Analiza raznosa tlaka pri uporabi prilagodljivega pridrževala z možnostjo nadzora pridrževalne sile med globokim vlekom - Jerman, Boris (Strojniški vestnik, 2001)
One of the most important parameters in the deep-drawing process is the force holding the blank. In a desire to improve the quality with products of complex geometries, forming technology has focused developments on better time-and place control of the holding force. For a more efficient location control of the holding force it is necessary to replace highly rigid blank holders with pliable or segmented blank holders. This paper discusses the holding conditions when a pliable blank holder of thickness 30 mm presses against the blank with 16 hydraulic cylinders during the process of forming a test product. The results of the research show the local distributions of pressure acting on the blank for a sequence of states during the process, taking into account the changes in the shape and the thickness of the blank.
Keywords: globoki vlek; pridržala; sile pridrževanja; analize uporabnosti